Beta-mangostin from Cratoxylum arborescens activates the intrinsic apoptosis pathway through reactive oxygen species with downregulation of the HSP70 gene in the HL60 cells associated with a G0/G1 cell-cycle arrest. Issue 11 (October 2017) - Omer, Fatima Abdelmutaal Ahmed; Hashim, Najihah Binti Mohd; Ibrahim, Mohamed Yousif; Dehghan, Firouzeh; Yahayu, Maizatulakmal; Karimian, Hamed; Salim, Landa Zeenelabdin Ali; Mohan, Syam
Xanthones are phytochemical compounds found in a number of fruits and vegetables. Characteristically, they are noted to be made of diverse properties based on their biological, biochemical, and pharmacological actions. Accordingly, the apoptosis mechanisms induced by beta-mangostin, a xanthone compound isolated from Cratoxylum arborescens in the human promyelocytic leukemia cell line (HL60) in vitro, were examined in this study. The 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay was done to estimate the cytotoxicity effect of β-mangostin on the HL60 cell line. Acridine orange/propidium iodide and Hoechst 33342 dyes and Annexin V tests were conducted to detect the apoptosis features. Caspase-3 and caspase-9 activities; reactive oxygen species; real-time polymerase chain reaction for Bcl-2, Bax, caspase-3, and caspase-9 Hsp70 genes; and western blot for p53, cytochrome c, and pro- and cleavage-caspase-3 and caspase-9 were assessed to examine the apoptosis mechanism. Cell-cycle analysis conducted revealed that β-mangostin inhibited the growth of HL60 at 58 µM in 24 h. The administration of β-mangostin with HL60 caused cell morphological changes related to apoptosis which increased the number of early and late apoptotic cells. The β-mangostin-catalyzed apoptosis action through caspase-3, caspase-7, and caspase-9 activation overproduced reactive oxygen species which downregulated the expression of antiapoptotic genes Bcl-2 and HSP70. Conversely, the expression of the apoptotic genes Bax, caspase-3, and caspase-9 were upregulated. Meanwhile, at the protein level, β-mangostin activated the formation of cleaved caspase-3 and caspase-9 and also upregulated the p53. β-mangostin arrested the cell cycle at the G0 /G1 phase. Overall, the results for β-mangostin showed an antiproliferative effect in HL60 via stopping the cell cycle at the G0 /G1 phase and prompted the intrinsic apoptosis pathway.